2012
DOI: 10.1038/ni.2255
|View full text |Cite
|
Sign up to set email alerts
|

The earliest thymic T cell progenitors sustain B cell and myeloid lineage potential

Abstract: The stepwise commitment from hematopoietic stem cells in the bone marrow (BM) to T lymphocyte-restricted progenitors in the thymus represents a paradigm for understanding the requirement for distinct extrinsic cues during different stages of lineage restriction from multipotent to lineage restricted progenitors. However, the commitment stage at which progenitors migrate from the BM to the thymus remains unclear. Here we provide functional and molecular evidence at the single cell level that the earliest progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 48 publications
8
146
3
1
Order By: Relevance
“…3A, 3B). An earlier report showed that ETPs were IL-7Ra 2/lo (36), whereas another group reported that ETPs expressed IL-7Ra (37). By flow cytometry, we demonstrated that ETPs expressed the IL-7Ra at intermediate levels (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…3A, 3B). An earlier report showed that ETPs were IL-7Ra 2/lo (36), whereas another group reported that ETPs expressed IL-7Ra (37). By flow cytometry, we demonstrated that ETPs expressed the IL-7Ra at intermediate levels (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…It was initially thought that thymic settling progenitors lost myeloid potential before acquiring either T or B potential but a few recent studies showed that some progenitors within the thymus had lost B potential while retaining myeloid potential [49][50][51]. These data raised some controversy as it was questioned as to whether this myeloid differentiation occurs under physiological conditions within the thymus itself [52,53] but it was very recently reported that ETPs give rise to the majority of thymic granulocytes [54].…”
Section: Hematopoietic Precursor Differentiation Within the Thymusmentioning
confidence: 99%
“…It will be important to determine whether the administration of donor HSCs by a combined IV/IT approach will promote a robust and long-lasting donor-derived thymopoiesis with an efficient donor-derived differentiation of other blood lineage cells (right panel). derived thymic settling cells that normally seed the thymus [51], with the former harboring T, B, granulocyte-macrophage (GM), and megakaryocyte-erythroid potential [61]. Furthermore, it has recently been elegantly shown that thymusautonomous T-cell differentiation can be sustained in mice with combined mutations in Rag2 together with either c-Kit or cc [58,59].…”
Section: (B)mentioning
confidence: 99%
“…Most developing B cells generate autoreactive Igs, which are selectively removed, resulting in only 20% autoreactivity in circulating naive mature B cells (17). Early thymic progenitors have been shown to sustain B cell potential (18,19), and in some studies progenitor B cells have been detected in human thymus (10,11). Moreover, the Ig gene repertoire of thymic B cells was found to be distinct from pediatric B cells from BM, and more similar to fetal B cells with regard to usage of V H 1-2 and V H 6-1 genes, although thymic B cells contained longer IgH-CDR3 regions than did fetal B cells (12,13).…”
Section: mentioning
confidence: 99%